Molecular epidemiology of coagulase-negative bloodstream isolates: detection of Staphylococcus epidermidis ST2, ST7 and linezolid-resistant ST23 - Adrián Martínez-Meléndez (Brazilian Journal of Infectious Diseases, 2016)
The mechanisms contributing to persistence of coagulase-negative staphylococci are diverse; to better understanding of their dynamics, the characterization of nosocomial isolates is needed. Our aim was to characterize phenotypic and molecular characteristics of Staphylococcus epidermidis and Staphylococcus haemolyticus human blood isolates from two tertiary care hospitals in Mexico, the Hospital Universitario in Monterrey and the Hospital Civil in Guadalajara.Antimicrobial susceptibility was determined. Biofilm formation was assessed by crystal violet staining. Detection of the ica operon and Staphylococcal Cassette Chromosome mec typing were performed by PCR. Clonal relatedness was determined by Pulsed-fiel gel electrophoresis and Multi locus sequence typing.Methicillin-resistance was 85.5% and 93.2% for S. epidermidis and S. haemolyticus, respectively. Both species showed resistance >70% to norfloxacin, clindamycin, levofloxacin, trimethoprim/sulfamethoxazole, and erythromycin. Three S. epidermidis and two S. haemolyticus isolates were linezolid-resistant (one isolate of each species was cfr+). Most isolates of both species were strong biofilm producers (92.8% of S. epidermidis and 72.9% of S. haemolyticus). The ica operon was amplified in 36 (43.4%) S. epidermidis isolates. SCCmec type IV was found in 47.2% of the S. epidermidis isolates and SCCmec type V in 14.5% of S. haemolyticus isolates. No clonal relatedness was found in either species. Resistance to clindamycin, levofloxacin, erythromycin, oxacillin, and cefoxitin was associated with biofilm production for both species (p < 0.05). A G2576T mutation in 23S rRNA gene was detected in an S. haemolyticus linezolid-resistant isolate. All linezolid-resistant S. epidermidis isolates belonged to ST23; isolate with SCCmec type IV belonged to ST7, and isolate with SCCmec type III belonged to ST2. This is the first report of ST7 in Mexico.There was a high genetic diversity in both species, though both species shared characteristics that may contibute to virulence. Keywords: Linezolid resistance, Staphylococcal Cassette Chromosome mec, Coagulase-negative staphylococci, Multilocus Sequence Typing